Interviews for the assessment of long-term incapacity for work: a study on adherence to protocols and principles - van Dijk Frank JH; Wind Haije; de Boer Wout EL; Willems Han HBM (BMC, 2009)
Abstract Background Assessments for long-term incapacity for work are performed by Social Insurance Physicians (SIPs) who rely on interviews with claimants as an important part of the process. These interviews are susceptible to bias. In the Netherlands three protocols have been developed to conduct these interviews. These protocols are expert- and practice-based. We studied to what extent these protocols are adhered to by practitioners. Methods We compared the protocols with one another and with the ICF and the biopsychosocial approach. The protocols describe semi-structured interviews with comparable but not identical topics. All protocols prescribe that the client's opinion on his capacity for work, and his arguments, need to be determined and assessed. We developed a questionnaire to elicit the adherence SIPs have to the protocols, their underlying principles and topics. We conducted a survey among one hundred fifty-five experienced SIPs in the Netherlands. Results Ninety-eight SIPs responded (64%). All respondents used some form of protocol, either one of the published protocols or their own mix. We found no significant relation between training and the use of a particular protocol. Ninety percent use a semi-structured interview. Ninety-five percent recognise having to verify what the claimant says and eighty-three percent feel the need to establish a good relation (p = 0.019). Twelve topics are basically always addressed by over eighty percent of the respondents. The claimant's opinion of being fit for his own work or other work, and his claim of incapacity and his health arguments for that claim, reach a hundred percent. Description of claimants' previous work reaches ninety-nine percent. Conclusion Our study shows professional consensus among experienced Dutch SIPs about the principle of assessment on arguments, the principle of conducting a semi-structured interview and the most crucial interview topics. This consensus can be used to further develop a protocol for interviewing in the assessment of incapacity for work in social insurance. Such a protocol can improve the quality of the assessments in terms of transparency and reproducibility, as well as by enabling clients to better prepare themselves for the assessments.